De morbis (Practica) puerorum atribuido a Gordonio (siglo XV): análisis comparativo entre Vaticanus Latinus 10213, fol. 541r(a-b) y Ms. Sloane 71, fols. 81r-83v - Domínguez Rodríguez, María Victoria (Ágora: estudos clássicos em debate, 2021)
This paper presents an analysis and comparative study between the Latin version of De morbis (Practica) puerorum ( Vaticanus Latinus 10213) and one of its Middle English translations (Ms. Sloane 71). It aims at establishing the extent to which both texts depend on each other, considering that, even though attributing them to his authorship could be a strategy to achieve auctoritas , there is also some evident interference from other works by Gordon. We also include a transcription of the Middle English translation, since it has so far gone unnoticed for scholars of this medieval doctor.